Implementasi Standard Operating Procedure Penitipan Barang Tamu dalam Mendukung Kualitas Layanan Concierge di Hotel Park Hyatt Jakarta. - Yayan Sugiarto; Soraya Kenita Rose (JURNAL PARIWISATA VOKASI, 2026)
This study aims to analyze the implementation of the Standard Operating Procedure (SOP) for guest luggage storage in supporting Concierge service quality at Park Hyatt Jakarta. A descriptive quantitative approach was employed using observation, interviews, documentation, and questionnaires involving 13 Concierge employees. Data were analyzed using descriptive statistics based on technical, administrative, and procedural aspects. The findings indicate that SOP implementation has not been consistently applied across all aspects. Inconsistencies mainly occur in technical procedures, administrative documentation, and compliance with operational procedures, particularly during high operational activity. The study concludes that Concierge service quality is determined not only by the availability of SOPs but also by their consistent implementation through reliability, traceability, and service standardization. These three elements form the foundation for improving service quality in hotel Concierge operations